Decreased specific antibody synthesis in old adults: Decreased potency of antigen-specific B cells with aging - Burns, Edith A.; Lum, Lawrence G.; Seigneuret, Margaret C.; Giddings, Bernadette R.; Goodwin, James S. (Mechanisms of ageing and development, 1990)
The rise in rates of infection in adults over the age of 60 is accompanied by a decreased ability of older adults to make specific immune responses after immunization with a variety of specific antigens (Ag). This investigation delineates age-related changes in Ag-specific humoral immunity, comparing adults over age 60 to young adults aged 18–40, using tetanus toxoid (TT) as an immunologic probe. A culture system which does not require TT booster immunizations of study subjects was used to induce in vitro specific antibody responses. The amount of anti-TT antibody (Ab) produced in serum and in culture was measured by a TT-specific enzyme-linked immunosorbent assay (ELISA). The numbers of anti-TT Ab-secreting B cells were measured by a TT-specific ELISA-plaque assay. The TT-specific responses of old subjects were significantly less than that seen for young control subjects in the following measures: (1) serum anti-TT Ab titers (mean ± S.E. log 2 titer = 3.3 ± 1.1 vs. 9.5 ± 1.4, P < 0.01); (2) anti-TT Ab produced by peripheral blood lymphocytes (PBL) in cultures stimulated with TT (6 ± 2.1 ng/ml vs. 22 ± 8.4 ng/ml, P < 0.01); (3) numbers of anti-TT Ab secreting B cells per million cells culured (6.7 ± 3.4 vs. 26.6 ± 7.6, P < 0.001) and (4) mean ng Ab secreted per anti-TT Ab-secreting B cell (0.6 ± 0.4 ng vs. 12.7 ± 7.8 ng, P < 0.01). This study shows that both decreased numbers of Ag-specific immune B cells and decreased potency on a per cell basis contribute to the impaired immune responses to immunizations in older adults.